Antimicrobial resistance and virulence profiles of staphylococci isolated from clinical bovine mastitis - Yang, Feng; Shi, Wenli; Meng, Na; Zhao, Yiyu; Ding, Xuezhi; Li, Qinfan (Frontiers in Microbiology, 2023)
Staphylococci, mainly including Staphylococcus aureus and coagulase-negative staphylococci (CNS), are one of the most common pathogens causing bovine mastitis worldwide. In this study, we investigated the antimicrobial resistance and virulence profiles of staphylococci from clinical bovine mastitis in Ningxia Hui Autonomous Region of China. Antimicrobial resistance was determined by disc diffusion combined with E-test method. Genes of antimicrobial resistance and virulence factors were determined by PCR. A total of 332 staphylococcal isolates were confirmed from 1,519 mastitic milk samples, including 172 S. aureus and 160 CNS isolates. Fifteen CNS species were identified, with S. chromogenes being the most frequent found (49.4%), followed by S. equorum (13.8%). Noticeably, 2 S. agnetis isolates were found among the CNS isolates. To our knowledge, this is the first report documenting the presence of S. agnetis from bovine mastitis in China. The S. aureus and CNS isolates showed high resistance against penicillin, followed by erythromycin and tetracycline. Multidrug resistance was found in 11.6 and 16.3% of the S. aureus and CNS isolates, respectively. Resistance to penicillin was attributed to the presence of blaZ, erythromycin resistance to ermC (alone or combined with ermB) and tetracycline resistance to tetK (alone or combined with tetM). Notably, one S. equorum isolate and one S. saprophyticus isolate were both methicillin-resistant and mecA positive. Additionally, all S. aureus isolates carried the adhesin genes fnbpA, clfA, clfB, and sdrC, and most of them contained cna and sdrE. Conversely, only a few of the CNS isolates carried clfA, cna, and fnbA. Regarding toxin genes, all S. aureus isolates harbored hlb, and most of them were hlg positive. The lukE-lukD, lukM, sec, sed, sei, sen, seo, tst, seg, seh, and sej were also detected with low frequencies. However, no toxin genes were observed in CNS isolates. This study reveals high species diversity of staphylococci from clinical bovine mastitis in Ningxia Hui Autonomous Region of China. The findings for the genetic determinants of antimicrobial resistance and virulence factor provide valuable information for control and prevention of staphylococcal bovine mastitis.